2018
DOI: 10.3892/etm.2018.6867
|View full text |Cite
|
Sign up to set email alerts
|

Association of vitamin�D receptor expression with inflammatory changes and prognosis of asthma

Abstract: The expression level of vitamin D receptor in patients with asthma was investigated to study the association between vitamin D receptor and inflammatory changes in asthma. Thirty patients with bronchial asthma treated in the Tianjin Hospital of ITCWM Nankai Hospital were selected as the experimental group, while 30 healthy individuals were selected as the control group. The mRNA expression level of vitamin D receptor in blood was detected via reverse transcription-quantitative polymerase chain reaction (RT-qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…The studies of various international groups, reported (TNF-alpha) genes, are already identified and the known locus of it might influence the inflammatory activity. Consequently, latest studies reported that TNF-alpha is one of the genes that play a leading role in the disease development [26] The study by Chen and Xu (2018) was against our observation, which found that TNF-α was higher, while TGF-β was lower in asthmatics than control [27], and surprisingly, a recent study done by Han et al (2021) showed that IGF-1 has a beneficial role in asthmatic adults and is associated with better pulmonary functions [28]. However, the study of Mu et al (2019) proved that IGF-1 is elevated in the lungs and BAL of asthmatic mice and it inhibits phagocytosis and development of apoptotic cells after lung injury, and after using blocking antibodies to IGF-1, phagocytosis, and apoptosis improved that ultimately lead to a decrease inflammatory cells infiltration and improvement of asthma [9].…”
Section: Discussioncontrasting
confidence: 61%
“…The studies of various international groups, reported (TNF-alpha) genes, are already identified and the known locus of it might influence the inflammatory activity. Consequently, latest studies reported that TNF-alpha is one of the genes that play a leading role in the disease development [26] The study by Chen and Xu (2018) was against our observation, which found that TNF-α was higher, while TGF-β was lower in asthmatics than control [27], and surprisingly, a recent study done by Han et al (2021) showed that IGF-1 has a beneficial role in asthmatic adults and is associated with better pulmonary functions [28]. However, the study of Mu et al (2019) proved that IGF-1 is elevated in the lungs and BAL of asthmatic mice and it inhibits phagocytosis and development of apoptotic cells after lung injury, and after using blocking antibodies to IGF-1, phagocytosis, and apoptosis improved that ultimately lead to a decrease inflammatory cells infiltration and improvement of asthma [9].…”
Section: Discussioncontrasting
confidence: 61%
“…We recently reported the inhibition of cellular oxidative stress effects and inflammation by vitamin D in non-irradiated, and UV radiated fibroblasts [29]. Vitamin D had been reported to inhibit oxidative stress, inflammation, angiogenesis and ECM remodeling in diverse cell types or tissue [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. We herein extend the beneficial effects of vitamin D to melanoma cells.…”
Section: Discussionmentioning
confidence: 96%
“…Likewise, related to food allergens, we found a statistically significant positive correlation between vitDs level and tIgE, and sIgE ≥ 3 class on hen's egg yolk and hen's egg white (p = 0.006), which we consider to be interdependence. Several studies investigated the relationship between vitamin D deficiency and allergic diseases and concluded that low level of vitamin D is associated with increased incidence of allergies and asthma [16,17,18]. Poole et al [19] in their study conducted on infants showed that vitamin D insufficiency is associated with an increased risk of a challenge-proven peanut/egg allergy.…”
Section: Discussionmentioning
confidence: 99%